Social Phenomena Between Local Transmigrant Communities and Regional Transmigrant Communities (1994-2020) in Kasimpa Jaya Village, Kec. South Tiworo, Kab. West Muna) - Ridayat Ridayat; Saefur Rochmat; Laode Ali Basri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Writing this paper aims to provide an overview or social phenomena on the pattern of community relations from social interactions between local transmigrant communities and regional migrants. Social interactions are dynamic social relationships that involve the relationship between people and individuals, between groups of people, as well as individuals and groups of people. The formulation of the problem in writing this scientific paper is how the social phenomena in the relationship pattern of social interactions that occur between the indigenous transmigrant community (Muna) and the immigrant transmigrant community (Bali). The method used in this writing uses qualitative exploratory research with observation data collection techniques, interviews and documentation.   The result of this paper is that the social phenomena in the relationship patterns of social interactions that exist in Kasimpa Jaya Village run very well and harmoniously between local transmigrant communities influenced by their development by the regional transmigrant community both in adopting the behavior, mindset and lifestyle of the local community itself, vice versa.